WATERBORNE POLYSTYRENE MICROPLASTIC EXPOSURE DEPRESSES GROWTH PERFORMANCE OF SIAMESE FIGHTING FISH (Betta splendens) - Wahyu Budi Utomo, Lalu; SETYONO, Bagus Dwi Hari; Affandi, Rangga Idris (Journal of Fish Nutrition, 2026)
This study evaluated the effects of waterborne polystyrene microplastic exposure on the growth performance of Siamese fighting fish (Betta splendens) over a 45-day rearing period. A completely randomized design with four treatments and three replicates was applied: 0, 50, 100, and 150 mg/L. The evaluated growth variables comprised absolute length gain, specific length growth rate, absolute weight gain, specific growth rate, feed conversion ratio (FCR), and survival rate (SR). Data were analyzed using one-way ANOVA followed by Tukey’s test at the 5% significance level. Polystyrene microplastic exposure significantly affected absolute length gain, specific length growth rate, absolute weight gain, and specific growth rate (p < 0.05). Fish reared without microplastic exposure consistently showed the highest growth performance, whereas the 150 mg/L treatment produced the lowest values across the principal growth endpoints. By contrast, FCR tended to increase with increasing microplastic concentration, but the effect was not statistically significant (p > 0.05). SR remained 100% in all treatments, indicating that the tested exposure levels produced sublethal rather than lethal effects under the present experimental conditions. Water quality remained within a range generally tolerated by betta fish, suggesting that the observed response was more closely associated with microplastic exposure than with overt deterioration of the rearing medium. Overall, waterborne polystyrene microplastic exposure reduced the growth performance of B. splendens and should be considered a relevant emerging stressor in ornamental fish culture.